Female Genital Mutilation in Sierra Leone: Forms, Reliability of Reported Status, and Accuracy of Related Demographic and Health Survey Questions - Owolabi Bjälkander; Donald S. Grant; Vanja Berggren; Heli Bathija; Lars Almroth (Hindawi Limited, 2013)
Objective. To determine forms of female genital mutilation (FGM), assess consistency between self-reported and observed FGM status, and assess the accuracy of Demographic and Health Surveys (DHS) FGM questions in Sierra Leone. Methods. This cross-sectional study, conducted between October 2010 and April 2012, enrolled 558 females aged 12-47 from eleven antenatal clinics in northeast Sierra Leone. Data on demography, FGM status, and self-reported anatomical descriptions were collected. Genital inspection confirmed the occurrence and extent of cutting. Results. All participants reported FGM status; 4 refused genital inspection. Using the WHO classification of FGM, 31.7% had type Ib; 64.1% type IIb; and 4.2% type IIc. There was a high level of agreement between reported and observed FGM prevalence (81.2% and 81.4%, resp.). There was no correlation between DHS FGM responses and anatomic extent of cutting, as 2.7% reported pricking; 87.1% flesh removal; and 1.1% that genitalia was sewn closed. Conclusion. Types I and II are the main forms of FGM, with labia majora alterations in almost 5% of cases. Self-reports on FGM status could serve as a proxy measurement for FGM prevalence but not for FGM type. The DHS FGM questions are inaccurate for determining cutting extent.